Envelope proteins of two HIV-1 clades induced different epitope-specific antibody response. Issue 12 (14th March 2018) - Shrivastava, Tripti; Samal, Sweety; Tyagi, Ashish K.; Goswami, Sandeep; Kumar, Naresh; Ozorowski, Gabriel; Ward, Andrew B.; Chakrabarti, Bimal K.
Highlights: More than 50% of global HIV-1 infected population is infected with clade C virus. The efficiently cleaved 4-2.J41 Env selectively binds to neutralizing antibodies. The soluble 4-2.J41-gp140-foldon proteins bind to broadly neutralizing antibodies. DNA prime/protein boost with clade C, 4-2.J41 Env elicited conformation-dependent antibodies. DNA prime/protein boost with clade B, JRFL Env primarily induced anti-V3 antibody. Combination of Envs elicited V3-directed antibodies without increasing neutralization breadth. Antigenicity of individual immunogen is important for multiclade HIV-1 Env-based vaccine. Abstract: Using HIV-1 envelope protein (Env)-based immunogens that closely mimic the conformation of functional HIV-1 Envs and represent the isolates prevalent in relevant geographical region is considered a rational approach towards developing HIV vaccine. We recently reported that like clade B Env, JRFL, membrane bound Indian clade C Env, 4-2.J41 is also efficiently cleaved and displays desirable antigenic properties for plasmid DNA immunization. Here, we evaluated the immune response in rabbit by injecting the animals with plasmid expressing membrane bound efficiently cleaved 4-2.J41 Env followed by its gp140-foldon (gp140-fd) protein boost. The purified 4-2.J41-gp140-fd protein is recognized by a wide panel of broadly neutralizing antibodies (bNAbs) including the quaternary conformation-dependent antibody, PGT145 with high affinity. We have also evaluated and compared the quality of antibody response elicited in rabbits after immunizing with plasmid DNA expressing the membrane bound efficiently cleaved Env followed by gp140-fd proteins boost with either of clade C Env, 4-2.J41 or clade B Env, JRFL or in combination. In comparison to JRFL group, 4-2.J41 group elicited autologous as well as limited low level cross clade neutralizing antibody response. Preliminary epitope-mapping of sera from animals show that in contrast to JRFL group, no reactivity to either linear peptides or V3-loop is detected in 4-2.J41 group. Furthermore, the presence of conformation-specific antibody in sera from animals immunized with 4-2.J41 Env is observed. However, unlike JRFL group, in 4-2.J41 group of animals, CD4-binding site-directed antibodies cannot be detected. Additionally, we have demonstrated that the quality of antibody response in combination group is guided by JRFL Env-based immunogen suggesting that the selection and the quality of Envs in multicade candidate vaccine are important factors to elicit desirable response.